Organ Pencernaan dan Status Escherichia coli Usus Puyuh yang Diberi Tepung Defatted Maggot (Hermetia illucens) sebagai Pengganti Meat Bone Meal - Vita Kurnia Citra; Widya Hermana; Rita Mutia (Institut Pertanian Bogor, 2019)
This study was designed to evaluate the effect of substitution of Meat Bone Meal (MBM) with defatted maggot (Hermetia illucens) meal (DMM) on weight and length of digestive organs and the status of Escherichia coli in quail intestine. This study used 285 female quails aged six weeks with an average weight of 153.3±3.7 g. This experiment used Completely Randomized Design with three treatments, five replications, and each replication consisteds of 19 quails. The treatments were P1 = 0% DMM in diet, P2 = 3.1% TDM in diet (to substitute 50% of MBM protein), and P3 = 6.18% TDM in diet (to substitute 100% of MBM protein). The measurement of the digestive organs was performed by weighing each of the digestive organ and compared with the live weight multiplied by 100%. The measurement of the relative length was calculated by comparing the length of the organs by live weight and multiplied by 100%. The calculation of the concentration of E. coli used the method of dilution according to Waluyo (2005). The results showed that there was no significant effect on the percentage and the relative length of digestive organs. Defatted maggot meal has the activity as a natural antimicrobial that can decrease the Escherichia coli in quail intestine by 99.99% along with the increase in defatted maggot meal to 6.18% in diet. It can be concluded that protein from defatted maggot (Hermetia illucens) meal can be used up to 6.18% as an alternative to replace MBM without alteration in health status of the quail.